Continuous Monitoring of the Thermoregulatory Response in Endurance Horses and Trotter Horses During Field Exercise: Baselining for Future Hot Weather Studies - Verdegaal, Elisabeth-Lidwien J. M. M.; Howarth, Gordon S.; McWhorter, Todd J.; Boshuizen, Berit; Franklin, Samantha H.; Vidal Moreno de Vega, Carmen; Jonas, Stacey E.; Folwell, Louise E.; Delesalle, Catherine J. G. (Frontiers in Physiology, 2021)
Establishing proper policies regarding the recognition and prevention of equine heat stress becomes increasingly important, especially in the face of global warming. To assist this, a detailed view of the variability of equine thermoregulation during field exercise and recovery is essential. Thirteen endurance horses and 12 trotter horses were equipped with continuous monitoring devices (gastrointestinal (GI) pill, heartrate (HR) monitor and global positioning system) and monitored under cool weather conditions during four endurance rides over a total of 80 km (40 km loops) and intense trotter track-based exercise over 1540 m. Recordings included GI temperature (Tc), speed, HR and pre- and post-exercise blood values. A temperature time profile curve of Tc was constructed, and a net area under the curve was calculated using the trapezoidal method. Metabolic heat production and oxygen cost of transport were also calculated in endurance horses. Maximum Tc was compared using an independent samples t-test. Endurance horses (mean speed 14.1 ± 1.7 km h-1) reached mean maximum Tc (39.0 ± 0.4°C; 2 x 40 km in 8 horses) during exercise at 75% of completion of Tc exercise and Tc returned to baseline within 60 minutes into recovery. However, the mean Tc was still 38.8 ± 0.4°C at a HR of 60 bpm which currently governs ‘fit to continue’ competition decisions. Trotters (40.0 ± 2.9 km h-1) reached a comparable mean max Tc (38.8 ± 0.5°C; 12 horses) always during recovery. In 30 % of trotters, Tc was still > 39°C at the end of recovery (40 ± 32 minutes). The study shows that horses are individuals and thermoregulation monitoring should reflect this, no matter what type of exercise is performed. Caution is advised when using HR cut-off values to monitor thermal welfare in horses since we have demonstrated how Tc can peak quite some time after finishing exercise. These findings have implications for training and management of performance horses to safeguard equine welfare and to maximize performance.